Rare bird documentation form for Peregrine Falcon at Saylorville Dam, 1985 - Moore, Francis L.et al (1985)
Rare bird documentation form for a Peregrine Falcon at Saylorville Dam in Polk County, IA on September 21, 1985. Epson - sheet feed